PENGARUH TINGKAT KESEHATAN BANK DENGAN METODE CAMELS TERHADAP PERTUMBUHAN LABA PADABANK UMUM SYARIAH PERIODE 2011-2014 - RAHMA NOVITASARI, DIAN (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACKThis study aimed to analyze the influence health of the bank with a CAMELS ratio to profit growth in the period of 2011-2014 on Islamic Banks. Financial ratios used are CAR, NPF, ROA, and FDR. This research uses secondary data from company financial statements. Data were analyzed using classic assumption test, multiple linear regression analysis, and hypothesis testing. The results obtained from simultaneous testing showed that the CAR, NPF, ROA, and FDR significant effect on earnings growth. While the partial test results indicate that CAR and FDR did not have a significant effect on earnings growth, but the NPF and ROA have significant influence.Keywords: health of the banks, CAMELS, profit growth